PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PEMBUATAN POLA DASAR BADAN WANITA DENGAN SISTEM DRAPING - Anggia Sekarini Yosanti (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
Purose of the study to find out the steps to delevlop videomedia making body pattern woman with draping system. Research development using team theory puslijaknov which includes 5 stages namely product analsyis to be developed, develop the intial product, validation exprest and revisions, small scale trials and revisions, large-scale trials and products end. Reserarch instruments use sheet use of media in learning. Techique descriptive analysis. Research result shows the development of video media learning through: product analysis that is requirements for the type of developments. Step observations to reveal the use of the syllabus analysis and analysis of developing media, the intial product is the process of making a video validation process for experst to find out the feasibility of the media, test small scale implementation of learning use video that was revoked 2 observer with good results, large scale test implementation of learning using video which was observed by observers with the results are very good.